An overview of the multidimensionality of Academic Engagement in language learning and how it has been investigated in the Saudi EFL context - Alsaadi, Haya Mohammed (Journal of English Language Teaching and Applied Linguistics, 2026)
This systematic review presents the multidimensional nature of academic engagement in language learning, with a particular focus on how it has been investigated the Saudi EFL context. Drawing on a wide range of theoretical and empirical studies, the review synthesizes key perspectives on academic engagement as a dynamic and context-dependent construct encompassing behavioral, cognitive, emotional, and social dimensions. The review highlights how engagement is closely linked to learners’ motivation, self-efficacy, and academic achievement, and how it functions as a mediator between instructional practices and learning outcomes. The review further explores major theoretical frameworks, including engagement theory and self-determination theory, to explain how learners’ psychological needs and classroom environments influence their involvement in language learning. Evidence from recent research in the Saudi EFL context indicates that factors such as online learning environments, teacher support, learner autonomy, and the use of language learning strategies significantly contribute to enhancing student engagement. Moreover, the findings suggest that engagement is not only a predictor of academic success but also a key factor in promoting positive emotional and social experiences in language classrooms. Despite the growing interest in this area, the review identifies a relative scarcity of comprehensive research addressing all dimensions of engagement in the Saudi EFL context. The study concludes by emphasizing the importance of adopting a holistic approach to engagement in language learning and calls for further empirical research to explore its multidimensional nature across different learning settings.